Beyond compliance: How financial reporting practices shape tax behavior among growing MSME’S - Sari, Nur Zeina Maya; Sondari, Tanty; Hadiana, R. Nana (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study examines the influence of entrepreneurial attitude on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with financial reporting compliance as a mediating variable and religiosity and patriotism as moderators. A survey of 500 MSME owners in West Java, Central Java, and East Java was conducted. The results show that a strong entrepreneurial attitude, which is marked by proactiveness and responsibility, positively affects tax compliance. Financial reporting compliance significantly mediates this relationship, as orderly financial reporting leads to better tax compliance. Additionally, religiosity and patriotism strengthen the link between entrepreneurial attitude and tax compliance, as business owners who uphold moral and national values are more likely to fulfill their tax obligations. These findings offer practical implications for policymakers, highlighting the need to enhance financial literacy, promote ethical entrepreneurship, and provide tax education grounded in social and national values.